Five ways to get a grip on designing medical student clerkship clinical rotations during a pandemic - Chen, K Jean; Wilson, Samuel; Cheung, Warren (Canadian Medical Education Journal, 2022)
During the COVID-19 pandemic, the task of preparing students for workplace-based clerkship and supporting learners’ ongoing professional identity formation became incrementally more challenging. The former design of clerkship rotations was re-challenged and revolutionized going forward, as COVID-19 accelerated the development and implementation of e-Health and technology-enhanced learning (TEL). However, the practical integration of learning and teaching activities, and the application of well-thought-out first principles in pedagogy in higher education, remain difficult to implement in today’s pandemic era. In this paper, using the transition-to-clerkship (T2C) course as an example, we outline the steps taken to implement our clerkship rotation, discussing various curricular challenges from the lenses of various stakeholders, and practical lessons learned.